Characterization Of Inextensible Flows Of Spacelike Curves With Sabban Frame In S12 - Ergut, Mahmut; Turhan, Essin; Korpinar, Talat (Soc Paranaense Matematica, 2013)
In this paper, we study inextensible flows of spacelike curves on S-1(2). We obtain partial differential equations in terms of inextensible flows of spacelike curves according to Sabban frame on S-1(2).
Keywords: Inextensible flows; Sabban Frame